The study examined the effectiveness of intense special exercises, combined with intermittent electrical stimulation, in alleviating lower back pain in professors aged 50-60 years at the College of Science, University of Baghdad - Essam , Farah; salam, karam (Journal of Physical Education, 2024)
Lower back pain is one of the problems facing all groups of society, especially the elderly, as the causes of pain revolve around many different factors. The research aims to use intense special exercises accompanied by intermittent electrical stimulation to get rid of lower back pain among professors of the College of Science at the University of Baghdad for ages 50–60 and identify its effect. The research assumes that there are statistically significant differences in the degree of pain before and after the therapeutic approaches. The research sample consisted of professors who suffer from constant pain, numbering (6). The researchers used the experimental method to design one experimental group with a pre- and post-test to suit the research problem. They also used the SPSS program to process the research data statistically. The collected results concluded that the intense special exercises and intermittent electrical stimulation at the beginning of the rehabilitation unit contributed to pain relief by reducing the degree of pain within a short period. The researchers recommended using special exercises and stimulation to relieve pain in other similar cases.